Peran Alur dan Setting Melalui Konflik dalam Novel “Bumi Manusia” Karya Pramoedya Ananta Toer - Anggun Putri Maharani; Imam Ma'ruf Fauzan; Ahmad Fahyumi (Lingua Franca, 2024)
This study aims to analyze the role of plot and setting in depicting conflict in the novel Bumi Manusia by Pramoedya Ananta Toer. The novel, which is the first part of the Buru Tetralogy, is about the struggle against social, economic, and cultural injustice during the Dutch colonial period. With a descriptive qualitative approach, this study uses the theories of plot, setting, and conflict as an analytical framework to explore the interaction of narrative elements that build the story. The results show that the plot in this novel is progressively designed to develop personal, social, and colonial conflicts. These conflicts reflect the inequality of the colonial system that affects the main character's life. In addition, the geographical, temporal, and cultural settings provide contexts that strengthen the intensity of the conflicts, such as through biased colonial courts and social stratification in society. The interaction between plot and setting not only produces an evocative narrative, but also shows a deep critique of colonial oppression and discrimination. This research contributes to the study of Indonesian literature by providing a new understanding of the way narrative elements are used to reflect historical and social struggles in literary works.